(untitled) (CIPEEX, 2024)
The COVID-19 pandemic has propelled telehealth in the healthcare sector, increasing the demand for digital solutions for appointment scheduling and communication between doctors and patients. Ultravital emerges as software aimed at streamlining these processes, offering convenience and security to patients. The main objective of Ultravital is to simplify the scheduling of medical appointments, providing patients with a convenient way to book their hospital visits. Additionally, it aims to facilitate communication between doctors and patients, allowing for the exchange of messages and comments through the platform. In this way, Ultravital aims to optimize the patient experience, especially for those with mobility limitations, the elderly, and individuals with busy schedules. The methodology adopted by Ultravital involves the implementation of data security measures, such as encryption of information in transit and at rest, proper authentication, and restricted access policies. Furthermore, it is necessary to integrate the software with the hospital’s scheduling system to ensure the availability of time slots and prevent scheduling conflicts. Finally, it is essential for patients to have internet access and a connected device to use Ultravital. With Ultravital, it is expected that patients will have a more convenient experience when scheduling medical appointments, avoiding the need for travel or phone calls. The efficient communication provided by the platform allows patients to ask questions, receive guidance, and provide relevant additional information to their doctors. Additionally, the software offers a calendar that assists in organizing medical schedules, displaying dates of scheduled appointments, examination days, and result delivery deadlines. Thus, Ultravital contributes to a more efficient and satisfactory healthcare experience.